Additive Manufacturing of a Miniature Functional Trocar for Eye Surgery - Lussenburg, Kirsten; Scali, Marta; Sakes, Aimée; Breedveld, Paul (Frontiers in Medical Technology, 2022)
Stereolithography is emerging as a promising additive manufacturing technology for a range of applications in the medical domain. However, for miniature, medical devices such as those used in ophthalmic surgery, a number of production challenges arise due to the small size of the components. In this work, we investigate the challenges of creating sub-millimeter features for a miniature, functional trocar using Stereolithography. The trocar cannula system is used in eye surgery to facilitate a passage for other instruments. A standard trocar consists of a hollow cannula and a flexible check valve. The research was performed in two stages: in the first stage we investigated the effect of different materials and print settings on the current design of the cannula and the valve separately, and in the second stage we used these findings to optimize the design and production process. After the first investigation, it became apparent that even though the dimensions of the trocar are within the feature size range of Stereolithography, all hollow features tended to fuse shut during printing. This effect appeared regardless of the materials or print settings, and can be attributed to refraction of the laser source. In order to circumvent this, we identified two potential strategies: (1) increasing the negative space surrounding features; and (2) decreasing the surface area per layer. By applying these strategies, we tested a new design for the cannula and valve and managed to 3D print a functional trocar, which was tested in an artificial eye. The design of the 3D printed trocar allows for further personalization depending on the specific requirements of both patient and surgeon. The proposed strategies can be applied to different applications to create miniature features using Stereolithography.